PENGARUH LAMA PEMASAKAN BIJI TERHADAP RENDEMEN DAN SIFAT FISIKO-KIMIA MINYAK KEMIRI - Erra Yusnita; B Wiyono; Hartoyo Hartoyo (Pusat Penelitian dan Pengembangan Hasil Hutan, 2001)
Kemiri (Aleuritus mollucana Willd) plants are widely distributed in the tropical and sub tropical regions. Meanwhile, kemiri plant grows vastly almost anywhere in Indonesia. Kemiri nut meg can be used not only as food-seasoning, ingredients but also as a traditional medicine. The kernel portion of kemiri nut has high nutrition and energy (calorific) values, and so does its oil. The nut, is the meat part after removing the kemiri thell, could is further produced oil after having undergone certains extractions process.Kemiri nut oil has such specific characteristics that being easily dried under open air. Therefore, this oil can be used as volatilizing agent in the manufactures of paint and varnish.In addition, the properties of kemiri nut oil are affected by its extraction methods and quality of its raw material (kemiri nut). In this regard, the study is conducted to learn the effect of cooking duration on the yield and physico-chemical propertiesof the resulting oil. The aim of this study is to find out the optimal cooking duration capable of producing oil with satisfactory qualities.The results reveal that increase in the cooking duration are affected significantly the yield, specific gravity, light transmittion, free fatty acid (FFA) content, and iod number of the oil. Cooking duration for 30 minutes turned out to give optimum condition with respect to oil properties, i.e. yield at 49,94%, iod number = 158.657; FFA = 1.1399; specific gravity = 0.9211, and transmittion = 70.43.Keywords : yield, physico-chemical properties, cooking duration.